DIMENSIKU: Integrasi Etnomatematika Betawi dalam Pembelajaran Matematika untuk Siswa Kelas V SD - Nabilah Mumtaz; Annasya Syiffa Syahida (Proceeding of Silampari Conference of Life Science and Technology, 2026)
This article presents the results of a needs analysis conducted as the initial stage in designing DIMENSIKU, an ethnomathematics-based learning application for fifth-grade elementary students in Kramat Jati District, East Jakarta. The study employed the Analysis stage of the ADDIE model through observation, semi-structured interviews, questionnaires, and documentation in three elementary schools. Quantitative data were obtained from students’ mathematics achievement records, while qualitative data were collected from teachers and students. The findings indicate that students still experienced difficulties in understanding plane geometry concepts conceptually, although learning outcomes varied across schools. Mathematics instruction remained dominated by conventional methods with limited use of interactive media and had not integrated Betawi cultural contexts into learning activities. The needs analysis identified the necessity for digital learning media that are interactive, contextual, and aligned with elementary students’ characteristics. These findings provide the foundation for designing DIMENSIKU as a mathematics learning application integrating Betawi ethnomathematics into plane geometry learning